A Lithium‐Ion Battery with Enhanced Safety Prepared using an Environmentally Friendly Process. Issue 11 (9th May 2016) - Mueller, Franziska; Loeffler, Nicholas; Kim, Guk‐Tae; Diemant, Thomas; Behm, R. Jürgen; Passerini, Stefano
Abstract: A new lithium‐ion battery chemistry is presented based on a conversion–alloying anode material, a carbon‐coated Fe‐doped ZnO (TMO‐C), and a LiNi1/3 Mn1/3 Co1/3 O2 (NMC) cathode. Both electrodes were fabricated using an environmentally friendly cellulose‐based binding agent. The performance of the new lithium‐ion battery was evaluated with a conventional, carbonate‐based electrolyte (ethylene carbonate:diethyl carbonate–1 m lithium hexafluorophosphate, EC:DEC 1 m LiPF6 ) and an ionic liquid (IL)‐based electrolyte ( N ‐butyl‐ N ‐methylpyrrolidinium bis(trifluoromethanesulfonyl)imide–0.2 m lithium bis(trifluoromethanesulfonyl)imide, Pyr14 TFSI 0.2 m LiTFSI), respectively. Galvanostatic charge/discharge tests revealed a reduced rate capability of the TMO‐C/Pyr14 TFSI 0.2 m LiTFSI/NMC full‐cell compared to the organic electrolyte, but the coulombic efficiency was significantly enhanced. Moreover, the IL‐based electrolyte substantially improves the safety of the system due to a higher thermal stability of the formed anodic solid electrolyte interphase and the IL electrolyte itself. While the carbonate‐based electrolyte shows sudden degradation reactions, the IL exhibits a slowly increasing heat flow, which does not constitute a serious safety risk. Abstract : Friendly and safe batteries ! A lithium‐ion full‐cell employing a LiNi1/3 Mn1/3 Co1/3 O2 cathode, a carbon‐coated iron‐doped zinc oxide anode and an ionic‐liquid‐based electrolyte is presented. Both electrodes were prepared using an environmentally friendly aqueous process. Compared to carbonate‐based electrolytes, the use of an IL electrolyte significantly enhances the safety of this new battery configuration.